Ancient DNA of Phoenician remains indicates discontinuity in the settlement history of Ibiza. Issue 1 (December 2018) - Zalloua, Pierre; Collins, Catherine; Gosling, Anna; Biagini, Simone; Costa, Benjamí; Kardailsky, Olga; Nigro, Lorenzo; Khalil, Wissam; Calafell, Francesc; Matisoo-Smith, Elizabeth
Abstract Ibiza was permanently settled around the 7th century BCE by founders arriving from west Phoenicia. The founding population grew significantly and reached its height during the 4th century BCE. We obtained nine complete mitochondrial genomes from skeletal remains from two Punic necropoli in Ibiza and a Bronze Age site from Formentara. We also obtained low coverage (0.47X average depth) of the genome of one individual, directly dated to 361–178 cal BCE, from the Cas Molí site on Ibiza. We analysed and compared ancient DNA results with 18 new mitochondrial genomes from modern Ibizans to determine the ancestry of the founders of Ibiza. The mitochondrial results indicate a predominantly recent European maternal ancestry for the current Ibizan population while the whole genome data suggest a significant Eastern Mediterranean component. Our mitochondrial results suggest a genetic discontinuity between the early Phoenician settlers and the island's modern inhabitants. Our data, while limited, suggest that the Eastern or North African influence in the Punic population of Ibiza was primarily male dominated.